A REVIEW OF HEALTHCARE CENTER - Siti Nur Fadhilah binti Masrom; Phang Yook Ngor; Ruzanita Mat Rani (Journal of Islamic, Social, Economics and Development, 2022)
Healthcare center is the first place people go when they need medical assistance. InMalaysia, healthcare is mainly under the Ministry of Health. The Malaysian governmentprioritizes healthcare growth and development and allocates some of the government's socialdevelopment budget to public health care. Hence, public healthcare is available to allMalaysian citizens. For citizen, the fee for registration at public hospitals and clinics are almostfree but patients can still receive the best treatment, medications, and services. So, the mainpurpose of this study is to illustrate a general review of the healthcare center in Malaysia. Therehave several points to elaborate which are the healthcare center, the healthcare team, thequality of the healthcare system, the Donabedian model, the dimensionless wellness, the patientcare, the outpatient department as the primary care, primary care, and service at the outpatientdepartment. There have 51 articles or theses of research were included in this paper. Weclassify papers according to the areas of application that are clear in the literature given thatseveral papers propose or illustrate general approaches.